2004
DOI: 10.1093/ajcn/80.6.1558
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and antioxidant activity of tea flavanols after consumption of green tea, black tea, or a green tea extract supplement

Abstract: Our observations suggest that green tea extract supplements retain the beneficial effects of green and black tea and may be used in future chemoprevention studies to provide a large dose of tea polyphenols without the side effects of caffeine associated with green and black tea beverages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
175
2
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(197 citation statements)
references
References 16 publications
11
175
2
9
Order By: Relevance
“…Studies on bioavailability are often conducted collecting specimens at timed intervals (after ingestion). Various studies have been conducted using normally prepared green tea beverages [14][15][16], ingested green tea extract (total catechins) [14,17,18], or ingestion of specific catechins [19][20][21]. These studies have shown that ECG and EGCG, and metabolites of EC and EGC can be detected and measured in blood plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on bioavailability are often conducted collecting specimens at timed intervals (after ingestion). Various studies have been conducted using normally prepared green tea beverages [14][15][16], ingested green tea extract (total catechins) [14,17,18], or ingestion of specific catechins [19][20][21]. These studies have shown that ECG and EGCG, and metabolites of EC and EGC can be detected and measured in blood plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Catechins -EGCG, (−)-epigallocatechin (EGC), (−)-epicatechin-3-gallate (ECG), and (−)-epicatechin (EC)-are important components of green tea ( Fig. 1: A, C) (11). EGCG is the most abundant polyphenol in green tea.…”
Section: Introductionmentioning
confidence: 99%
“…1: B, C) (11,19). TFDG possesses two galloyl groups as a result of the polymerization of two EGCG molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant TFs in black tea are theaflavin (TF1), TF-3-O-gallate (TF2A), TF-3′-Ogallate (TF2B), and TF-3,3′-O-digallate (TF3), which are synthesized with different combinations of precursors. 1) TFs have several catechin-like properties, such as antioxidative 2,3) and antivirus 4) activities, with some being equal to 2) or stronger 4) than those of catechins. Bitter taste receptors (TAS2Rs) are known to respond to bitter substances.…”
mentioning
confidence: 99%